Growth of Peanut Plants (Arachis Hypogaea) using Paitan Weed Compost Fertilizer (Tithonia Diversifolia) Combined with Buffalo Kohe - Sulpa, Agriati; P, Jamaluddin; Rahmah , Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research was to determine the effect of fertilizer application on the growth of peanut plants (Arachis hypogaea) using compost from paitan weed (Tithonia diversifolia) combined with buffalo kohe and to analyze the concentration of compost from paitan weed (Tithonia diversifolia) combined with buffalo kohe. offers peanut plants (Arachis hypogaea) the best interaction for growth. This research used a single factor Complete Randomized Block Design (RAKL). The concentration of compost fertilizer is the determining factor for paitan (Tithonia diversifolia) combined with buffalo kohe with three replications per experimental unit, with P_0 = 0 kg/m^2 (control), P_1 = 1 kg/m^2, P_2 = 1, 5 kg/m^2, P_3 = 2 kg/m^2, P_4 = 2, 5kg/m^2, and P_5 = 3kg/m^2.